PERANCANGAN PRINT AD SEBAGAI MEDIA KAMPANYE “THE BENEFITS OF EATING FISH” DI PROVINSI SUMATERA BARAT - NANDA SEPTIAN DARMA PUTRA, Dr. Budiwirman, M.Pd. Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
One of the wealth natural resources on earth is the vast sea. One of them is Indonesia. Indonesia is maritime country which most of its territory is the sea. The sea is very influential in human life. Many benefits and purpose in the sea especially the organism in there particullary a fish. Fish are organism are has habitat on the water not only that, this animal also belong in the food chain of human because it has animal protein. Which has a lot of protein and nutrient, fatty acid, omega 3, vit D and B2, calcium, phosphor, minerals, zing, iodine, magnesium, and potassium are important for human growth.The purpose of this final work is to inform the benefits contained in the fish means of prints ad with the concept interesting and education to Print Ad “The Benefits of Eating Fish”. The author use design method ranging from collecting data through observation interview, and followed by using the method of data analysis using SWOT analysis (Strength, Weakness, Opportunity, Treatment). The next author began a creative design. In designing print ad the author displays layout, typography, illustration, and attractive color that match the print Ad “The Benefit of Eating Fish”.Print Ad attractive design will be special attraction for the target audience to see and read information on the benefit of fish in print Ad to increase competent knowledge and resources.Keyword : Print Ad, benefits of eating fish.